Modification of Apremilast from Pills to Aerosol a Future Concept - Paul Zarogoulidis (MDPI AG, 2021)
Background: Inhaled drugs have been available in the market for several years and for several diseases. Drugs for chronic obstructive pulmonary disease, cystic fibrosis, and diabetes have been used for several years. In the field of drug modification, these drugs range from tablets to aerosol. Methods: Milling as used to break down the tablets to powder and nebulisers are used to produce aerosol droplets. A mastersizer was used to measure the mass median aerodynamic diameter of the aerosol droplets. Results: Apremilast produced mmad diameters (2.43 μm) without any statistical difference between the different jet-nebulizers. The residual cup B contributed to greater mmad diameters as the 95% interval of mean values, based on those the ANOVA mean square clearly indicated, followed by cups C and F. The previous interval plot is much better clarified when the interaction means between drug and residual cap are plotted. The residual cups B, C and F produce mmad between (2.0–3.2). Conclusion: In the current research study we demonstrated our methodology to create apremilast powder and produce apremilast aerosol droplets with different nebulisers and residual cups.